Tikrieji ir funkciniai beasmeniai veiksmažodžiai dabartinėje lietuvių kalboje - Katkuvienė, Laima (Baltistica, 1989)
IMPERSONAL VERBS PROPER AND IMPERSONALLY USED PERSONAL VERBS IN MODERN LITHUANIAN The aim of the paper is to investigate the grammatical and semantical properties of impersonal verbs, to discuss the relations between impersonal verbs proper, impersonally used personal verbs and impersonal reflexive verbs. From the morphological point of view impersonal verbs proper distinguish themselves by the fact that they are not conjugated for person and number and occur only in the 3rd person singular form. Impersonal verbs proper are characterized by certain syntactic peculiarities: their infinitives can never be used as subjects or objects in a sentence. On the semantic plane these verbs denote an agentless state or process, never an action. The relations between impersonal verbs proper and impersonally used personal verbs are treated in terms of the notion of polylexeme. Impersonal reflexive verbs constitute a specific class of verbs different both from impersonal verbs proper and impersonally used personal verbs.